2022
DOI: 10.1038/s41467-022-28417-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential activation mechanisms of lipid GPCRs by lysophosphatidic acid and sphingosine 1-phosphate

Abstract: Lysophospholipids are bioactive lipids and can signal through G-protein-coupled receptors (GPCRs). The best studied lysophospholipids are lysophosphatidic acid (LPA) and sphingosine 1-phosphate (S1P). The mechanisms of lysophospholipid recognition by an active GPCR, and the activations of lysophospholipid GPCR–G-protein complexes remain unclear. Here we report single-particle cryo-EM structures of human S1P receptor 1 (S1P1) and heterotrimeric Gi complexes formed with bound S1P or the multiple sclerosis (MS) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 57 publications
3
75
3
Order By: Relevance
“…61 A data processing 'decoy' refinement strategy was implemented at this step to improve map resolution as described previously. 66 Micrographs were over-picked with particles using a Laplacian of Gaussian filter in Relion 3.0. 61 Particles were subjected to a round of reference-free 2D classification in cryoSPARC3.0 to remove ice contaminants.…”
Section: Expression and Purification Of Msp1d1mentioning
confidence: 99%
“…61 A data processing 'decoy' refinement strategy was implemented at this step to improve map resolution as described previously. 66 Micrographs were over-picked with particles using a Laplacian of Gaussian filter in Relion 3.0. 61 Particles were subjected to a round of reference-free 2D classification in cryoSPARC3.0 to remove ice contaminants.…”
Section: Expression and Purification Of Msp1d1mentioning
confidence: 99%
“…Of note is the conformation of Phe283 7.37 , which in the gauche+ conformation, like that observed in the crystal structures of CB 2 R, ,, closes the tunnel, whereas in the trans conformation, it opens it. Moreover, it has been shown that the N-terminus of the S1P 1 receptor packs against ECL-2 in the active conformation, leading to an opening of the ligand access vestibule between TMs 1 and 7 . Thus, we have quantified in Figure S3 the number of snapshots, during the 100 μs of MD simulation, in which Phe283 7.37 adopts the trans conformation or/and the distance between the top of TMs 1 (Cα atom of Thr34 1.33 ) and 7 (Cα atom of Val277 7.31 ) increases from the initial value of 14.5 Å to values larger than 15.5 Å. GPCRs are dynamic proteins that permit rapid small-scale structural fluctuations, and accordingly, both events can be freely observed, simultaneously or not, during the calculated trajectories (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…To rapidly construct effective S1PR1 agonists, we analyzed the binding mode of the representative compound BAF312 in detail. Three BAF312‐bound S1PR1 complex structures resolved by cryo‐EM have been disclosed (PDB ID: 7TD4, [ 25 ] 7EVY, [ 26 ] 7EO4, [ 27 ] Figure 2A). BAF312 exhibits the following conformational features: Hydrophobic tails consisting of benzene and cyclohexyl groups extend into the hydrophobic pockets with the trifluoromethyl substrates orienting towards the gap between TM5 and TM6 (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The molecular docking tool Glide module (maestro version 11.5) was used to dock BAF312 and compounds 9a — 9k to three BAF312 bound S1PR1 cryo‐EM structures (accession code in the Protein Data Bank: 7EVY, [ 26 ] 7EO4 [ 27 ] and 7TD4 [ 25 ] ).…”
Section: Methodsmentioning
confidence: 99%